PHYSICAL FACILITIES AVAILABILITY ON CHILDREN ATTENDANCE IN PUBLIC PRE-PRIMARY SCHOOLS IN MWATATE SUB-COUNTY, KENYA - Adline, Shinga Mkiwa; Ashiono, Benard L. (IJRDO-Journal of Applied Science, 2023)
The purpose of this study is to establish the influence of physical facilities availability on children attendance in public pre-primary schools in Mwatate Sub-County, Kenya. The study employed a descriptive survey research design. The target population for this study was 279 comprising of 184 Pre-Primary School teachers in 92 School Committee Chairpersons and 3 ECDE supervisors in three zones of Mwatate sub-county. The study employed a census method to determine the sample sizes of Pre-Primary School teachers (184) and ECDE supervisors (3); and a ten percent rule for School Committee Chairpersons (11). This gave a total sample size of 178 persons. Three instruments namely: the Pre-Primary School Teacher Questionnaire, School Committee Chairperson Interview and ECDE supervisors Interview Schedule was employed to collect data from the respondents. The instruments were validated by use of expert judgment while reliability of the tools was established through the use of test-retest procedures. Internal consistency of the tool was be established through the use of the Cronbach’s Alpha measures. The questionnaire was deemed to be reliable after attaining a reliability value of α = 0.88. Data was analyzed statistically using percentages and Chi-Square measures at 0.05 confidence levels. The study established that there is a statistically significant relationship between physical facilities availability and children attendance in public pre-primary schools in Mwatate Sub-County, Kenya. Overall, the study highlights the need for institutions and parents to work together to create a conducive learning environment for all children. This includes providing a variety of learning resources, maintaining clean and orderly classrooms and encouraging regular school attendance. By addressing these issues, institutions and parents can help ensure that all children have access to quality education and the opportunity to reach their full potential.